McMinn's interactive clinical anatomy - Abrahams, Peter H.; Mosby-Year Book. (London : Mosby, 1997)
(Producer) Images and text from several anatomy books are integrated and cross-linked. Includes additional clinical notes, problems and images, plus more than 200 video clips, a 3-D virtual dermatone map, and images from the 3-D Interactive skeleton.
CD is avaiable at Koleksi Media, Perpustakaan HUKM
Includes images and text from: A colour atlas of human anatomy / R.M.H. McMinn ... [et al.]. 3rd ed. London : Wolfe, c1993 and other books.
a System requirements: IBM or compatible PC, 486 DX-33 or higher processor; 8MB RAM; Windows; CD-ROM drive; soundcard; screen display, 640 x 480 (800 x 600 recommended); 256 col. display (65,000 colours strongly recommended).
Keywords: Anatomy -- CD-ROOM